GOOD CORPORATE GOVERNANCE (GCG) AND FINANCIAL DISTRESS BEFORE AND DURING THE PANDEMIC COVID-19 - Emilia, Rosintha; Windijarto (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: Companies need to apply Good Corporate Governance (GCG) to avoid financial difficulty during periods of crisis. This study can see more clearly the effect of the realization of GCG on banking during a crisis by comparing influence before the crisis and its influence during the crisis, is the application of GCG stronger in the crisis? And whether the show of GCG during a crisis can lower the occurrence of financial distress in affected firms. Methods: Quantitative research method using statistical analysis using regression panel data tested in different situations. Results: The effect of the GCG on financial distress increased in the crisis period, namely 25.48% in the pre-crisis term, increasing to 98.67% in the crisis term. Conclusion and suggestion: The outcome of this examination shows that GCG had a negative and significant effect before the crisis and during the crisis, but the results showed the influence of GCG is stronger for crisis periods where in that period companies will try to improve their corporate governance as an effort to survive.